Antibacterial and antifungal activities from leaf and bark extract of Cassine glauca (Rottb.) Kuntze - Dhanasekaran, K.; Ashok, Kishore Kumar; Balakrishnan, V. (Current Botany, 2025)
Practical knowledge of traditional medicine from ancient times, medicinal plants, often known as medicinal herbs, have an extensive history. Plants produce hundreds of different kinds of chemicals to serve various purposes, such as defense and protection against pathogens, fungi, insects, and herbivorous mammals.The present study investigates the antibacterial and antifungal potential of Cassine glauca leaves and bark extract. The antimicrobial activity was to find out in the extracts by using the agar disc diffusion method. Chloroform, ethanol and ethyl acetate extracts were obtained from the leaves and bark. It showed that antimicrobial activity against tested microbes from the four bacterial strains such as Staphylococcus aureus (MTCC 9542), E. coli (MTCC 732), Klebsiella pneumonia (MTCC 3040) and Proteus vulgaris (MTCC 7299) and three fungal strains such as Aspergillus niger (MTCC 1785), Aspergillus versicolor (MTCC 280) and Candida albicans (MTCC3958). The zone of inhibition of leaf and bark extracts were compared with standards like Ampicillin, Methicillin, and Norfloxacin for antibacterial and Terbinafine and nystatin for antifungal activity. The antimicrobial study result reveals that good inhibition of the bacterial and fungal grown against the tested microbes. The antimicrobial activity showed that to justify the use of their plant in traditional medicine and the practice of supplementary decoction.